Cost effectiveness analysis of rheumatoid arthritis outpatient at a hospital in bandung - Oskar Skarayadi; Wita Anggraeni; Pudjiastuti Kartidjo; Andri Reza Rahmadi; Suci Nar Vikasari (Institute of Computer Science (IOCS), 2023)
Rheumatoid arthritis is a chronic systemic autoimmune disease of the joints with unknown etiology. treatment therapy is carried out to reduce the symptoms of inflammation, one of which is by using methylprednisolone and methotrexate. treatment is carried out in the long term. this study aims to analyze the cost-effectiveness of combined methylprednisolone in rheumatoid arthritis patients. the study used a retrospective descriptive analytic design. the data were taken from 31 outpatient medical records in hasan sadikin hospital from january 2017-december 2018. the research data included the das28 score, doctor visit fees, medical expenses, and laboratory fees. cost-effectiveness analysis is done by calculating the average cost effectiveness ratio (acer) and incremental cost effectiveness ratio (icer). the results showed 17 patients using methylprednisolone+methotrexate, 6 patients using methylprednisolone+sulfasalazine, 1 patient using methylprednisolone+cyclosporine, 2 patients using methylprednisolone+methotrexate+chloroquine, 3 patients using methylprednisolone+chloroquine+cyclosporine and 2 patients using methylprednisolone+chloroquine. the lowest acer value was obtainedwhen the combination of methylpredisolone+chloroquine was rp. 453,716 per effectiveness with an icer value of rp. 11,686 per effectiveness. this study concludes that the combination of methylprednisolone + chloroquine is the most effective therapy compared to other combinations of methylprednisolone.